OBESITY, FAT TOPOGRAPHY AND RISK OF CARCINOMA BREAST - Khan, Ayesha; Rafique, Kashif; Farooq, Umer; Khan, Khalid (Journal of Ayub Medical College Abbottabad, 2017)
Background: Carcinoma breast is most common cancer and the leading cause of cancer related deaths in women, with a multifactorial aetiology. This case control study was aimed at studying the possible link of body fat with the pathogenesis of carcinoma breast. Methods: A case control study extending over a period of two years (2015-2016) was conducted in which the body size and shape of 56 carcinoma breast cases was studied against 168 controls who had no breast disease. Results: Fifty-six women suffering from carcinoma breast had a higher BMI and fat distributed in the abdominal area A high BMI was found to be protective in pre-menopausal women (OR= 0.14 by; 95% CI: 0.02-0.77) while it was a risk factor in post-menopausal women (OR=2.39 by; 95% CI: 1.02-5.55). Waist-to-hip ratio (WHR) of ‰¥0.9 was associated with an increased risk of carcinoma breast compared to WHR ‰¤0.8 (OR=3.857 by; 95% CI: 0.875-17.05). Conclusion: the results show there is an increased risk of carcinoma breast in women having more fat cantered around the abdomen. Keywords: postmenopausal; weight gain; fat distribution; fat topography; carcinoma breast; body mass index; body shape; obesity; central obesity